2021
DOI: 10.1016/j.bmc.2020.115927
|View full text |Cite
|
Sign up to set email alerts
|

Novel indolylarylsulfone derivatives as covalent HIV-1 reverse transcriptase inhibitors specifically targeting the drug-resistant mutant Y181C

Abstract: Non-nucleoside reverse transcriptase inhibitors (NNRTIs) are widely used in combination therapies against HIV-1. However, emergent and transmitted drug resistance compromise their efficacy in the clinical setting. Y181C is selected in patients receiving nevirapine, etravirine and rilpivirine, and together with K103N is the most prevalent NNRTI-associated mutation in HIVinfected patients. Herein, we report on the design, synthesis and biological evaluation of a novel series of indolylarylsulfones bearing acryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In this direction, several studies have been carried out for the design and synthesis of indole derivatives with CÀ S bonds for the evaluation of their medicinal importance. [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] In 2003, Silvestri et al [52] reported indolylarylsulfones, a nonnucleoside reverse transcriptase inhibitors (NNRTIs) as a potent anti-HIV-1 carrying NNRTI resistance mutations for the first time. The NNRTIs based anti-HIV agent have received significant attention due to their favorable pharmacokinetics properties and low toxicity.…”
Section: As Antiviral Agentmentioning
confidence: 99%
See 1 more Smart Citation
“…In this direction, several studies have been carried out for the design and synthesis of indole derivatives with CÀ S bonds for the evaluation of their medicinal importance. [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] In 2003, Silvestri et al [52] reported indolylarylsulfones, a nonnucleoside reverse transcriptase inhibitors (NNRTIs) as a potent anti-HIV-1 carrying NNRTI resistance mutations for the first time. The NNRTIs based anti-HIV agent have received significant attention due to their favorable pharmacokinetics properties and low toxicity.…”
Section: As Antiviral Agentmentioning
confidence: 99%
“…These results suggest the valuable idea for the design of new series of IAS NNRTIs with reduced neurotoxic effects and improved resistance profile against the mutant HIV-1 strains. [66][67][68][69]…”
Section: As Antiviral Agentmentioning
confidence: 99%
“…Also, stacking interactions with Phe227 and Pro236 amino acids is responsible for effective interaction. [71] Pribut and team reported several benzimidazolones hybrids against HIV strains. In the presence of clinically significant resistance strains, such as K103N and Y181C, compounds are nevertheless effective against HIV-1.…”
Section: Chemistryselectmentioning
confidence: 99%
“…Larger binding pocket of NNRTI in the mutant enzyme is probably responsible for appreciable interaction of compounds 12 and 13 (Figure 7). Also, stacking interactions with Phe227 and Pro236 amino acids is responsible for effective interaction [71] …”
Section: Role Of Nitrogen‐containing Heterocyclic Compounds In Inhibi...mentioning
confidence: 99%
“…Furthermore, Y181 is the most easily mutated amino acid in NNIBP, and a variety of mutant strains have been reported, including Y181C, Y181V and Y181I. These reported RT covalent inhibitors showed excellent activity against wild-type HIV-1 strain, but greatly reduced activity against mutant strains [ 8 , 9 , 10 ]. Therefore, covalent inhibitors targeting conserved amino acids were proposed to improve the anti-drug resistance in this work.…”
Section: Introductionmentioning
confidence: 99%